Feedback after summative OSCEs: optimising delivery and engagement - Soe, Myo Min (2020)
Background Few opportunities for learning exist after high stakes summative assessments. Providing students feedback after summative Objective Structured Clinical Examinations (OSCEs) could be a learning opportunity. However, as engagement is often poor, it is necessary to have an understanding of the learners’ perspective to design a summative feedback programme. Once summative feedback has been given, it is necessary to evaluate its quality and quantity and whether the learners engage with it as the examiners and learners may have little motivation and opportunity to engage with summative feedback.